Concentration of attention and creating a psychological characteristics of Czech national men team in biathlon - Ondracek, J.; Pacholik, V.; Paugschova, B.; Hrebickova, S.; Vitek, Z. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2012)
Physical, running and preparing of top biathletes in principle derives from a similar scenario, where in each phase of the preparatory period athletes receive alpine training on dry land, preparing on the first snow in optimal conditions, eg.at Dachstein, and the long phase of preparation in northern Scandinavia snow conditions. From there the biathletes usually go straight to the first WC races. Differences in the preparation or some reserves in preparation of individual athletes must therefore be look for t in shooting practice, and especially in the psyche of athletes in strengthening it and in the degree of level of mental preparation. Among technically, tactically and physically balanced competitors wins the one who is mentally doing better at the moment (Vitek, 2011). For the purposes of Czech men biathlon team we conducted several psychological tests so that they can be used by coaches to enhance the psychological state of athletes, especially with regard to the optimal management of the shooting part of the biathlon race. The aim of this initial investigation was to perform personality characteristics of athletes and determine their level of concentration of attention. Survey results should therefore be understood as an initial part of a comprehensive approach to strengthening the mental status of athletes in the field of biathlon shooting, because the best defense against the adverse effects of negative mental states occurring in the extreme conditions of sport training and competitions, is a sophisticated and consistently applied system of mental preparation.